Survey On Multihop Cluster Head Techniques in MODLEACH - Saini, Manpreet; Singh, Sukhbeer; Chouhan, Neelam (International Journal of Computer Sciences and Engineering, 2019)
MODLEACH is modified version of LEACH protocol, in this protocol, for every round, new cluster head is elected and hence new cluster formation is required. This paper gives the over view of Enhanced MODLEACH for cluster head selection. The data transfer in clusters among nodes depends upon the approach used, the intra cluster and inter cluster technique increases the network life. So this paper presents the data transfer techniques and clustering in MODLEACH protocol.